Temperature-dependence of L-type Ca(2+) current in ventricular cardiomyocytes of the Alaska blackfish (Dallia pectoralis) - Kubly, Kerry L. (J Comp Physiol B, 2015)
To lend insight into the overwintering strategy of the Alaska blackfish (Dallia pectoralis), we acclimated fish to 15°C or 5°C and then utilized whole-cell patch-clamp to characterize the effects of thermal acclimation and acute temperature change on the density and kinetics of ventricular L-type Ca(2+) current (I(Ca)). Peak I(Ca) density at 5°C (−1.1± 0.1 pA pF(−1)) was 1/8(th) that at 15°C (−8.8 ± 0.6 pA pF(−1)). However, alterations of the Ca(2+)- and voltage-dependent inactivation properties of L-type Ca(2+) channels partially compensated against the decrease. The time constant tau (τ) for the kinetics of inactivation of I(Ca) was ~4.5-times greater at 5°C than at 15°C, and the voltage for half-maximal inactivation was shifted from −23.3 ± 1.0 mV at 15°C to - 19.8 ± 1.2 mV at 5°C. These modifications increase the open probability of the channel and culminated in an approximate doubling of the L-type Ca(2+) window current, which contributed to approximately 15% of the maximal Ca(2+) conductance at 5°C. Consequently, the charge density of I(Ca) (Q(Ca)) and the total Ca(2+) transferred through the L-type Ca channels (Δ[Ca(2+)]) were not as severely reduced at 5°C as compared to peak I(Ca) density. In combination, the results suggest that while the Alaska blackfish substantially down-regulates I(Ca) with acclimation to low temperature, there is sufficient compensation in the kinetics of the L-type Ca(2+) channel to support the level of cardiac performance required for the fish to remain active throughout the winter.